Peningkatan Keterampilan Mahasiswa/i Melalui Penggunaan Virtual Laboratory pada Matakuliah Sainsmatika Semester 2 PIAUD di STAI Auliaurrasyidin Tembilahan - Dina Liana; Nurkamelia Mukhtar AH (STAI Auliaurrasyidin Tembilahan, 2020)
The purpose of the research is to explore the improvement of the students’ skills over Virtual Library on Sainsmatika at PIAUD Semester 2 students, STAI Auliaurrasyidin. Type of the research used is action research. It is a learning done in the classroom to improve learning process in the class. Data collection technique used in the research was test, observations, and documentation. The collected data was then analyzed descriptively. The analyzed data were data of students’ learning achievement and students’ scientific works. Based on the data, it can be stated that virtual library practices can improve the skills of the PIAUD, class A, semester 2 students on Scientific Studies. Material used was about digestive and respiratory system of fish, toads, lizards, birds, and mice.